The rhetorical methods in the poetry of Ahmad Rami - Dalya Muhi sekhi; Prof. Dr Mohammad Ali Hajalipour (Journal of College of Education, 2025)
This research examines the rhetorical methods in the poetry of Ahmad Rami, a prominent figure whose work has significantly impacted Arabic literature with its linguistic beauty and sophisticated expressions. The study aims to analyze the literary and artistic features that distinguish his poetic works, focusing on his use of rhetorical techniques, such as interrogation, imperative mood, vocative, and wishing style. It highlights how these techniques contribute to giving his poetry a unique and distinctive character, ensuring his immortalization in the Arabic literary tradition. A rhetorical analysis of his most notable poems is conducted to explore the depth and linguistic richness that characterize his work. The objective is to uncover the hidden connotations and meanings within these rhetorical styles and their effects on the audience. The study employs a descriptive-analytical method, leading to several key findings. Chief among them is the poet’s innovative use of rhetorical techniques, transforming them from their conventional linguistic meanings into new connotations imbued with emotional significance. For instance, commands may deviate from their original meanings to suggest guidance, reconciliation, wishes, or entreaty. The vocative may shift to convey longing, familiarity, grandeur, high status, yearning, or veneration. Interrogatives can express negation, wonder, affirmation, bewilderment, improbability, and disdain, while prohibitions may imply advice and guidance.